High brightness narrow-linewidth microsecond pulse green laser by frequency doubling of a master oscillator power amplifier Nd:YAG laser. (October 2018) - Zong, Qing-shuang; Bo, Yong; Guo, Chuan; Bian, Qi; Chang, Jin-quan; Li, Wen-jun; He, Li-jiao; Di, Peng-cheng; Zuo, Jun-wei; Shen, Yu; Cui, Da-fu; Peng, Qin-jun; et al.
Highlights: A high power μs long pulse green laser is well suited to pump Ti:sapphire laser. A 1064 nm Nd:YAG master oscillator power amplifier laser is used as a pump source. Using LBO, a 78.4 W 532 nm laser is obtained by frequency doubling of Nd:YAG laser. The laser is operating at 500 Hz repetition rate with a linewidth of 0.54 pm. The brightness of the green light is as high as 1.08 × 10 10 W/cm 2 sr. Abstract: We demonstrated a high brightness narrow-linewidth microsecond (μs) pulse green laser from second harmonic generation (SHG) of a master oscillator power amplifier (MOPA) laser system. The oscillator was a quasi-continuous wave pulsed diode-side-pumped 1064 nm Nd:YAG laser with an average output power of 45.2 W and a beam quality factor of M 2 = 1.21, operating at a pulse repetition frequency of 500 Hz with a ∼160 μs of pulse duration. After a two-stage amplifier, the fundamental output power of MOPA system was increased up to 198 W. Using a type-I lithium triborate nonlinear crystal, the maximum SHG output power of 78.4 W at 532 nm was obtained with a linewidth of 0.54 pm and a beam quality factor M 2 less than 1.61. The brightness of the green light was as high as 1.08 × 10 10 W/cm 2 sr. This is, to the best of our knowledge, the highest brightness solid state light source for the narrow-linewidth μs pulse green lasers at 532 nm.